Self-rebounding tubular composite heat-conducting pad based on metal aerogel and preparation method and application of self-rebounding tubular composite heat-conducting pad

Through the self-resistance tubular composite thermal pad based on metal aerogel, the problems of insufficient thermal resistance and elasticity in the chip package of existing thermal interface materials are solved, and the effects of lower thermal resistance and higher elasticity are achieved, improving the thermal management and reliability of the chip.

CN119570461AActive Publication Date: 2025-03-07HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411758508.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-07
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing thermal interface materials have problems such as thermal resistance, volatility and curing, insufficient mechanical resilience, poor electrical insulation, poor process compatibility, poor interface matching and long-term stability in chip packaging, which affects the thermal management effect and reliability.

Method used

Using a self-resistance tubular composite thermal pad based on metal aerogel, a tubular structure with liquid metal coated nanowires is formed by preparing metal hydrogels, blending liquid metal dispersion with citric acid ethanol solution, mixing with metal aerogel and standing soaking, resetting ethanol solution, drying and mechanical tailing, etc., to form a tubular structure with liquid metal coated nanowires to improve thermal conductivity and resilience.

Benefits of technology

It achieves lower thermal resistance, higher resilience and better electrical insulation, can effectively deal with the thermal expansion and cold shrinkage deformation of the chip, extend the working life of the chip, and avoid problems such as liquid pumping and flux volatility during the packaging process, improving production stability and performance reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570461A_ABST
    Figure CN119570461A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal interface materials, in particular to a self-rebounding tubular composite heat conduction pad based on metal aerogel as well as a preparation method and application of the self-rebounding tubular composite heat conduction pad. The self-rebound tubular composite heat-conducting pad prepared by the invention is a key material for guaranteeing stable heat dissipation of an electronic system in the field of semiconductors, is single in component, low in thickness (30 microns) of a bonding area, excellent in rebound resilience, free of flowability and anti-aging, does not have the phenomena of liquid pumping out, soldering flux volatilization and the like in the packaging process, and is suitable for large-scale production. The problems that a traditional heat-conducting silicone grease paste is aged and layered after being pumped out, a heat-conducting gasket is thick and high in heat resistance, and scaling powder volatilizes in the using process of an indium sheet can be solved, and therefore better production stability and performance reliability are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal interface materials, and in particular to a self-resilient tubular composite thermal conductive pad based on metal aerogel, and a preparation method and application thereof. Background Art

[0002] Thermal interface materials (TIM) play a vital role in the field of chip packaging, especially in high-performance and high-power density electronic devices. When the chip is working, a lot of heat will be generated. If it is not dissipated in time, the chip temperature will be too high, affecting performance and life, or even causing damage. In order to effectively transfer heat from the chip to the heat sink or cooling system, thermal interface materials are needed.

[0003] The main function of thermal interface materials is to provide a low thermal resistance connection layer between the chip (usually an integrated circuit made of silicon or other semiconductor materials) and the heat sink or heat sink. Since the surface of the chip and the heat sink cannot be completely flat, there are microscopic unevenness and gaps. These gaps will form an air layer, and the thermal conductivity of air is very low, which will greatly increase the thermal resistance. Thermal interface materials can fill these gaps and reduce the presence of air, thereby significantly improving the efficiency of heat conduction. Common thermal interface materials include thermal grease, thermal gel, silicone-free thermal pads, thermal phase change materials, thermal elastomer materials, thermal silicone cloth and carbon fiber thermal pads.

[0004] Although thermal interface materials (TIMs) provide a critical thermal management solution in the chip packaging field, they are not without technical flaws. Here are some common issues and challenges: (1) Thermal resistance: Although TIMs are designed to reduce thermal resistance, they themselves introduce additional thermal resistance. This is because thermal interface materials are generally not as good at thermal conductivity as direct contact materials such as metals, and they may form bubbles due to drying, aging or insufficient pressure, further increasing thermal resistance. (2) Volatility and curing: Some types of TIMs, such as thermal conductive pastes, may contain volatile components that may evaporate during long-term use, causing the material to dry out and increase thermal resistance. In addition, some liquid TIMs need to be cured to achieve optimal performance, and the curing process may be affected by environmental conditions such as temperature and humidity. (3) Mechanical resilience: TIMs must be able to withstand the thermal expansion and contraction of the chip during operation, as well as long-term thermal cycling. TIMs with poor mechanical resilience may crack or lose adhesion after multiple thermal cycles, delaminating from the chip or the heat, affecting the thermal management effect. (4) Electrical insulation: For applications that require electrical isolation, TIMs must have sufficient electrical insulation performance. However, some high-performance TIMs, such as liquid metal, may not have good electrical insulation, limiting their application in specific scenarios. (5) Process compatibility: Some TIMs may be difficult to be compatible with existing packaging processes. For example, liquid metal may corrode surrounding components, or some materials may decompose at high temperatures and release harmful gases. (6) Interface matching: The difference in thermal expansion coefficients between chips and heat sinks of different materials may cause interface stress. Improperly selected TIMs may not be able to fully relieve this stress, thereby affecting reliability. (7) Long-term stability: Over long-term use, the performance of TIMs may deteriorate, such as reduced thermal conductivity, changes in viscosity, etc., which may require regular inspection and maintenance.

[0005] In response to these technical shortcomings, researchers and manufacturers continue to work on developing new materials and technologies to improve the performance, stability and reliability of TIMs while reducing costs and environmental impact. Therefore, a new thermal interface material that can comprehensively solve the above problems is needed. Summary of the invention

[0006] The first aspect of the present invention provides a method for preparing a self-resilient tubular composite thermal pad based on metal aerogel, comprising the following steps:

[0007] S1. preparing a metal hydrogel, washing and drying the metal hydrogel to obtain a metal aerogel;

[0008] S2. dispersing the liquid metal in an ethanol solution of citric acid to obtain a mixture, blending the mixture with the metal aerogel and allowing it to stand and soak, and then resetting the mixture with an ethanol solution to obtain a metal hydrogel-based composite material;

[0009] S3. Drying the metal hydrogel-based composite material to obtain a metal aerogel-based composite material;

[0010] S4. The metal aerogel-based composite material is immersed in an ethanol solution of acetic acid for 5-20 minutes, and then reset by the ethanol solution, and the product is dried, mechanically cut, and laser processed to obtain the self-resilient tubular composite thermal pad;

[0011] The volume proportion of the liquid metal in the self-rebound tubular composite thermal conductive pad is 60-80%.

[0012] Further, the metal aerogel is prepared by: PVP, AgNO 3、 FeCl3 is dissolved in ethylene glycol and stirred evenly, then placed in a drying oven and heated for reaction to obtain nanosilver hydrogel, the nanosilver hydrogel is soaked in a NaBH4 aqueous solution, a new NaBH4 aqueous solution is replaced each time, and then soaked in alcohol; after cleaning, supercritical drying is performed to obtain silver nanowire aerogel.

[0013] The metal aerogel obtained by chemical method is a three-dimensional network structure composed of nanowires. Liquid metal particles enter the three-dimensional network structure by static immersion and adhere to the surface of the nanowires. The particles are in contact with each other and with the nanowires. The liquid metal has strong oxidizing properties and has an oxide shell on the surface. The presence of the oxide shell will hinder the conduction of heat. Therefore, the oxide shell of the liquid metal is destroyed by immersion in acetic acid, and the liquid metal particles are aggregated and wrapped on the surface of the nanowires, finally forming a tubular structure of liquid metal wrapped nanowires to obtain a self-resilient tubular composite thermal conductive pad.

[0014] In some embodiments, the metal material of the metal aerogel is at least one of silver, copper, nickel, gold, and tin.

[0015] In some embodiments, the liquid metal is selected from at least one of gallium indium, gallium indium tin, and gallium indium zinc.

[0016] In some embodiments, the melting point of the liquid metal is 3-40°C.

[0017] The fluidity of liquid metal at room temperature can promote the liquid metal to coat the surface of the nanowires to form a tubular structure, thereby improving the resilience of the aerogel, compensating for the volume shrinkage deformation generated when the new power chip is working, ensuring effective heat conduction, and extending the working life of the chip.

[0018] In some embodiments, the particle size of the liquid metal is 500 nm to 3 μm.

[0019] In some embodiments, the concentration of the ethanol solution of citric acid is 0.05-0.5 g / L.

[0020] In some embodiments, the concentration of the acetic acid ethanol solution is 1-8 vol%.

[0021] In some embodiments, the drying time in S3 is 0.5-5 hours.

[0022] In some embodiments, the liquid metal composite mass ratio is 30% to 80%.

[0023] The second aspect of the present invention provides a self-resilient tubular composite thermal pad based on metal aerogel, which is obtained by the above-mentioned preparation method.

[0024] In some embodiments, the thermal resistance of the self-resilient tubular composite thermal pad is 0.15°C·cm 2 / W, the rebound is 70%.

[0025] In some embodiments, the interior of the self-resilient tubular composite thermal pad is a three-dimensional network structure composed of nanowires, and the nanowires are a tubular structure wrapped in liquid metal.

[0026] The third aspect of the present invention provides the application of the self-resilient tubular composite thermal pad in the semiconductor field.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The self-rebounding tubular composite thermal pad prepared by the present invention is a key material to ensure stable heat dissipation of electronic systems in the semiconductor field. Different from the paste-like thermal grease and the traditional thermal pad (0.5mm) with higher modulus and larger thickness in the prior art, the new thermal pad of the present invention has a single component, a low thickness in the bonding area (30μm), no fluidity, and anti-aging. There is no liquid pumping out, flux volatilization and other phenomena in the packaging process. It can solve the pain points of traditional thermal grease paste pumping out, aging stratification, high thickness and high thermal resistance of thermal pads, and flux volatilization during the use of indium sheets, and thus has better production stability and performance reliability.

[0029] 2. The self-rebound tubular composite thermal pad prepared by the present invention has excellent resilience. The liquid metal is coated on the nanowire, which improves the mechanical strength of the nanowire, so that the aerosol composed of the nanowire has a certain resilience. The temperature change during the operation of the power chip causes the device to shrink and expand, etc. The thermal interface material with a certain high deformability and resilience can compensate for the deformation during operation and improve the adaptability of the package. By controlling the coating amount of the liquid metal, the rebound amount can be adjusted by 2% to 70%. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a microscopic image of the interior of the silver nanowire aerogel prepared in Example 1 before compounding the second phase.

[0031] Figure 2 Schematic diagram of the internal structure of the self-resilient tubular composite thermal pad prepared in Example 1.

[0032] Figure 3 The overall macroscopic image and local internal microscopic image of the self-resilient tubular composite thermal conductive pad prepared in Example 1. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a self-resilient tubular composite thermal pad based on metal aerogel, and the preparation method includes the following steps:

[0036] S1. Preparation of nanosilver aerogel by chemical in-situ reduction method: 0.2g PVP, 0.5g AgNO 3、 0.2gFeCl3 was dissolved in 50mL ethylene glycol and stirred evenly, then placed in a drying oven and reacted at 130°C for 4h to obtain nanosilver hydrogel. The nanosilver hydrogel was soaked in 0.002M NaBH4 aqueous solution for 5 times, 10min each time, and a new NaBH4 aqueous solution was replaced each time, and then soaked in alcohol for 10min; after cleaning, supercritical drying was performed to obtain silver nanowire aerogel. Silver nanowire aerogel is a three-dimensional network structure composed of silver nanowires. A 25mm*25mm*5mm silver aerogel preform was obtained by laser cutting. The microscopic picture of the interior of the aerogel is shown below: Figure 1 shown.

[0037] S2. Dissolve 0.03g of citric acid in 30ml of ethanol and stir thoroughly to obtain a citric acid ethanol solution. Then add 2g of liquid metal GaInSn into the citric acid ethanol solution, and ultrasonicate for 10min at a power of 200W to obtain a suspension of liquid metal GaInSn nanoparticles with a particle size range of 500nm-3um.

[0038] S3. The nanosilver aerogel obtained in S1 is immersed in the liquid metal nanoparticle suspension obtained in S2, and the mass ratio of GaInSn nanoparticles in the nanosilver hydrogel-based composite material is adjusted by controlling the standing time. When the standing time is 2h, the highest composite ratio is close to 80%.

[0039] S4. Then, the liquid metal suspension was replaced by immersion in an ethanol solution to obtain a nanosilver hydrogel-based composite material; the nanosilver hydrogel-based composite material was dried by supercritical carbon dioxide for 1 h to obtain a nanosilver aerogel-based composite material;

[0040] S5. Soak the nanosilver hydrogel-based composite material in an ethanol solution of acetic acid (5 vol%) for 10 min, then reset it with the ethanol solution, and dry the product to obtain a self-rebound tubular composite thermal pad. The schematic diagram of the self-rebound tubular composite thermal pad is shown in Figure 2 As shown, the overall macroscopic picture of the thermal pad is as follows Figure 3 (a) shows the microscopic image of the internal tubular structure. Figure 3 (b) as shown.

[0041] Example 2

[0042] This embodiment provides a self-resilient tubular composite thermal pad based on metal aerogel, and the specific implementation method is the same as that of Embodiment 1, except that:

[0043] S4. The composite hydrogel obtained in S3 is placed in an ethanol solution and ultrasonicated using an ultrasonic wave (power 30 W, frequency 20 kHz). The oxidation shell on the surface of the liquid metal particles is broken under ultrasonic vibration, and the liquid metals fuse with each other to wrap the silver nanowires to form a tubular structure, and then the remaining liquid metal suspension is replaced with an ethanol solution;

[0044] S5. The material obtained in S4 is subjected to supercritical carbon dioxide drying to finally obtain a self-resilient tubular composite thermal pad.

[0045] In addition to the comparison with Example 1, the ultrasonic crushing of liquid metal adopted in this example can improve the convenience of operation and avoid the possibility of invisible damage of acetic acid to the silver nanowires.

[0046] Comparative Example 1

[0047] The specific implementation of this comparative example is the same as that of Example 1, except that the liquid metal particles in S2 are GaIn, the ultrasonic power is 150 W, the concentration of the acetic acid ethanol solution in S5 is 2 vol%, and the immersion time is 10 min.

[0048] Comparative Example 2

[0049] The specific implementation of this comparative example is the same as that of Example 1, except that the liquid metal particles in S2 are GaIn, the ultrasonic power is 250 W, the concentration of the acetic acid ethanol solution in S5 is 7 vol%, and the immersion time is 20 min.

[0050] Comparative Example 3

[0051] The specific implementation of this comparative example is the same as that of Example 1, except that the ultrasonic power in S2 is 100 W, the concentration of the acetic acid ethanol solution in S5 is 10 vol%, and the immersion time is 5 min.

[0052] Comparative Example 4

[0053] The specific implementation of this comparative example is the same as that of Example 1, except that the liquid metal particles in S2 are Ga, the ultrasonic power is 100 W, the concentration of the acetic acid ethanol solution in S5 is 10 vol%, and the immersion time is 5 min.

[0054] Performance Testing

[0055] The composite materials prepared in the above examples and comparative examples were subjected to the following tests, and the results are shown in Table 1:

[0056] Thermal resistance: The thermal resistance of the material was tested using the total thermal resistance steady-state method using the interface material thermal conductivity and thermal resistance measuring device LW-9389 (LongWin Co., Ltd. China) designed based on the ASTM-D5470 standard test method.

[0057] Rebound elasticity: Tested using a mechanical machine, 5mm material is compressed to 30μm and then left to stand for 10s. The rebound distance is measured with a vernier caliper. The rebound distance / compression distance × 100% is calibrated as the rebound amount.

[0058] Table 1

[0059] Thermal resistance Resilience(%) Example 1 <![CDATA[0.15℃·cm 2 / W]]> 70 Example 2 <![CDATA[0.16℃·cm 2 / W]]> 72 Comparative Example 1 <![CDATA[0.4℃·cm 2 / W]]> 60 Comparative Example 2 <![CDATA[0.3℃·cm 2 / W]]> 65 Comparative Example 3 <![CDATA[0.25℃·cm 2 / W]]> 55 Comparative Example 4 <![CDATA[0.5℃·cm 2 / W]]> 45

[0060] It can be seen from the above performance test results that the self-resilient tubular composite thermal pad of Example 1 has excellent resilience and thermal conductivity. This is mainly because the three-dimensional thermal conductive network formed by the metal aerogel greatly improves the deformability of the composite thermal interface material and can exert excellent thermal conductivity. The liquid metal wrapped on the silver nanowires improves the mechanical strength of the material, thereby improving the resilience of the thermal pad.

[0061] However, the comparative example did not adopt the necessary technical solution, resulting in that it was significantly worse than the embodiment in the corresponding performance test. In comparative examples 1-4, the type of composite liquid metal, ultrasonic power, concentration of ethyl acetate and immersion time were changed. It can be seen that the conductive effect and the rebound effect were reduced to varying degrees, which proves that the solution of embodiment 1 has an important influence on the effect of the present invention.

[0062] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a self-resilient tubular composite thermal pad based on metal aerogel, characterized in that: The steps include: S1. preparing a metal hydrogel, washing and drying the metal hydrogel to obtain a metal aerogel; S2. dispersing the liquid metal in an ethanol solution of citric acid to obtain a mixture, blending the mixture with the metal aerogel and allowing it to stand and soak, and then resetting the mixture with an ethanol solution to obtain a metal hydrogel-based composite material; S3. Drying the metal hydrogel-based composite material to obtain a metal aerogel-based composite material; S4. The metal aerogel-based composite material is immersed in an ethanol solution of acetic acid for 5-20 minutes, and then reset by the ethanol solution, and the product is dried, mechanically cut, and laser processed to obtain the self-resilient tubular composite thermal pad; The volume proportion of the liquid metal in the self-rebound tubular composite thermal conductive pad is 60-80%.

2. The preparation method according to claim 1, characterized in that: The metal material of the metal hydrogel is at least one of silver, copper, nickel, gold and tin.

3. The preparation method according to claim 2, characterized in that: The particle size of the liquid metal is 500nm-3μm.

4. The preparation method according to claim 3, characterized in that: The concentration of the citric acid ethanol solution is 0.05-0.5 g / L.

5. The preparation method according to claim 4, characterized in that: The concentration of the acetic acid ethanol solution is 1-8 vol%.

6. The preparation method according to claim 5, characterized in that: The drying time in S3 is 0.5-5h.

7. A self-resilient tubular composite thermal pad based on metal aerogel, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 6.

8. The self-resilient tubular composite thermal pad according to claim 7, characterized in that: The thermal resistance of the self-resilient tubular composite thermal pad is 0.15°C·cm 2 / W, the rebound is 70%.

9. The self-resilient tubular composite thermal pad according to claim 7, characterized in that: The diameter of the tubular nanowire is 50nm-220nm, and the thickness of the liquid metal on the surface of the nanowire is 20-50nm.

10. Application of the self-resilient tubular composite thermal pad according to claim 7 in the semiconductor field.

Citation Information

Patent Citations

  • Preparation and packaging method of metal aerogel coated liquid metal heat-conducting adhesive

    CN112694858A

  • Preparation method of aluminum oxide aerogel based on liquid metal

    CN118684250A

  • Metal aerogel composite material and preparation method thereof

    CN119060540A

  • Large-surface-area, unsupported catalyst for electro-chemical processes and method for producing same

    US20150162622A1

  • Delayed activation of no-heat liquid solder in a wellbore

    US20210222513A1